The Open-Ended Problem Solving in Mathematics Class of Grade 6 Students - Pongpullponsak, Assoc.Adisak; Kulchantawit, Jiraporn (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2009)
The objective of this research was to study the result of open-ended problem solving methods in mathematics class instruction of Grade-6 students. Three open-ended problem solving activities had been implemented, including those activities related to geometry, arithmetic and problem solving skills, with 61 grade-6 students of Wat Chang Lek and Ras Padung Pol schools. The data collecting tools included evaluation and scoring criteria form, learning efficiency evaluation form and mathematic learning attitude evaluation form. The statistics tools included average value, standard errors, data presentation (table and descriptive). In learning efficiency comparison, the statistics term "t" was employed to compare learning efficiency of two groups of students. The result indicated that there was no difference in learning efficiency between two methods while the attitude in mathematics learning, with open-ended problem solving method, of the students in the experimental group was in "strongly agree" level. The thinking behavior, in problem solving by each aspect, of students in the same experimental group (in both small sub groups and individual) was in "good" level.